Daily Grape Juice Consumption Promotes Weight Loss, Improved Stability and Reduced the DNA Damage in the Elderly - Cañete da Costa Pedro; Stolzenberg Blembeel Amanda; Farias Wohlenberg Mariane; Gabardo Tatiane; dos Santos Lacerda Denise; Kneib Gonçalves Luciana; Mello Alexandre; Bortolato Gabrielli; Pereira Costa Leonardo; Dalpicolli Rodrigues Adriana; Veiga Cardoso Casali Valesca; Funchal Cláudia; et al. (International Journal of Nutrition, 2020)
The aim of this study was to determine the influence of chronic supplementation with grape juice (400ml), in modulating the anthropometric and biochemical parameters. Thirty-nine seniors participated and were evaluated at baseline after 30 days. The chronic consumption of grape juice reduced weight, BMI and waist circumference. Indeed, the consumption modulated biochemical parameters, decreased the total cholesterol levels, Low-density lipoprotein (LDL) cholesterol, Urea and GGT. In addition, the intake of juice improved the performance in the TUG test, and caused more stability in the elderly. The levels of protein oxidation declined and the antioxidant potential significantly increased as well as SOD and the ratio SOD / CAT. In contrast, levels reduced sulfhydryl groups to consumption. In nuclear changes there are a decrease in the frequency of MN and picnosis. In conclusion, grape juice could be an excellent option to improve quality of life in elderly.
Keywords: Functional food